Methodological interests and the teaching of research methods in Latin America - Piovani, Juan Ignacio (Sociologies in Dialogue.)
This article analyzes a series of historical processes related to the development of shared methodological interests within the community of Latin American social scientist. First, it illustrates how a specific methodological field emerged as part of the institutionalization and professionalization of the social sciences, especially in the US, and how the methodological concerns and debates changed over time. On the other hand, it describes the repercussions of these processes in Latin America, particularly for the emergence of a "scientific" sociology, and how the accumulation of experiences related to the methodological field led to the establishment of specialized institutions in the region, such as the Latin American Network of Social Science Methodology (RedMet). With regard to the methodological interests of Latin American academics, the article focuses on those that have been put forward in the regional congresses of social science methodology (ELMECS) organized biannually by RedMet and, in particular, on the problem of the teaching and learning of research methods, that has been a core concern in all the different countries and institutions. Within this broad interest related to the teaching of methodology, special attention is paid to the results of empirical research conducted on how methods are actually taught in varius PhD programs of differen Latin American universities from Argentina, Brazil and Mexico.